LOS MAMÍFEROS DE LA FORMACIÓN CASA GRANDE (EOCENO) DE LA PROVINCIA DE JUJUY, ARGENTINA (Ameghiniana, 2014)
In this paper the fossil mammalian fauna from the paleogene Casa Grande Formation (Jujuy Province, Argentina) is presented. Martinmiguelia fernandezi gen. et sp.nov. (Leontiniidae,NotounguIata) is bere described, based on cranial and mandibular remains. Its distinctive characters suggest tbat it is tbe most generalized Leontiniid known, adding new evidence on the early history of this group. Also other notoungulate remains pertaining to be family Isotemnidae are described, being represented by isolated upper teeth, and an incomplete lower jaw. Due to the incompleteness of these materials they are referred provisionally as Isotemnidae, indeterminate species A and B. The mammal fauna of tbe Casa Grande Formation, even fragmentary as it is, contributes to a better understanding of the evolutionary history of the Eogene Ungulate mammals from Northem Argentina. Also a tentative correlation is proposed between the Casa Grande Formation of Jujuy Province and the Geste Formation of Antofagasta de la Sierra at Catamarca Province. Tbe Casa Grande Formation is here referred to the Mustersan Age (Middle Eocene).